2021
DOI: 10.1111/psyg.12749
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness may mediate the relationship between depression and the quality of life among elderly with mild cognitive impairment

Abstract: Background: Depression and mild cognitive impairment (MCI) are often comorbid mental health issues in older adults. The current study explored the prospective mediating role of loneliness in the relationship between depression and the quality of life in elderly with MCI. A second aim was to examine differences in depression, loneliness, and the quality of life in the elderly with MCI among gender groups, and type of residence groups. Methods: A cross-sectional survey with purposive sampling was used. Older adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Mediation analysis was performed using the “lavaan” package from Rosseel 37 . Spearman correlation has been used to account for the non‐normality of all four mediators (loneliness and the three religious activity scores).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mediation analysis was performed using the “lavaan” package from Rosseel 37 . Spearman correlation has been used to account for the non‐normality of all four mediators (loneliness and the three religious activity scores).…”
Section: Methodsmentioning
confidence: 99%
“…Mediation analysis was performed using the "lavaan" package from Rosseel. 37 Spearman correlation has been used to account for the non-normality of all four mediators (loneliness and the three religious activity scores). Using the control variables dictated by the multivariate model selection procedure, we conducted a parallel mediation analysis to examine the mediating effect of a collection of uncorrelated mediators all at once.…”
Section: Statistical Analysis Planmentioning
confidence: 99%
“…It is estimated that more than 40% of elder people worldwide are lonely, especially as age increases 21,22 . In some studies, 7,23 it is stated that quality of life decreases with an increase in the feeling of loneliness, 20 and this is associated with a decrease in the level of physical activity 24 . The studies conducted on the elderly have found that physical activity significantly reduces loneliness 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Many factors have been found to be associated with depression among residents in LTC settings [ 9 , 10 , 11 , 12 , 13 ], including psychological distress or fear related to COVID-19 during this pandemic [ 14 ]. Loneliness is one of the common factors experienced among older people, and associated with depression [ 13 ] and a lower quality of life of residents in LTC settings [ 15 , 16 ]. Loneliness is the subjective feeling of lacking intimate and close relationships to others [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different measurements were developed according to different understandings about loneliness; The De Jong Gierveld Loneliness Scale (DJGLS) considers loneliness from three perspectives (types of loneliness, the perspective of time, and emotional aspects) [ 17 ]; the UCLA loneliness scale contains two dimensions, i.e., negatively and positively worded items [ 18 ]. Studies have shown that 11.6 to 85.3% of people living in LTC settings have experienced loneliness [ 15 , 19 ]. Factors associated with loneliness include living alone, being unsatisfied with life, being at risk for undernutrition, having mental problems, having a weak sense of coherence, and not having contact with neighbors [ 19 ].…”
Section: Introductionmentioning
confidence: 99%